Penanaman Karakter Tanggung Jawab Siswa di SD Negeri 133/VI Rejosari II - Syafa'atin, Shinta Isnaini; Sintya, Maya; Lestari, Fadila Puji; Anggreyani, Risma; Kusuma, Framesti Putri Intan; Haryanti, Meli (Lembaga Yasin AlSys, 2023)
Education has a close relationship with the teaching and learning process. School is a place where learning takes place where teachers and students carry out teaching and learning activities. In education, a student should be balanced with a balanced character education. One example of character development carried out in the curriculum is responsibility. Responsibility is an attitude of being committed, independent, and able to fulfill their duties properly. The purpose of making this article is to analyze the characterization of the responsibility of students at SDN 133/VI Rejosari II. This research was conducted at SDN 133/VI Rejosari II using a qualitative research type with a descriptive method. The conclusion is that the cultivation of character education from an attitude of responsibility is important. The factors that influence the character of responsibility in elementary school students can come from external factors and internal factors. Internal factors include self-awareness possessed by elementary school students. While external factors can come from the influence of television, cellphones, or peers. So that in this case, parents must be able to provide some values of responsibility, advice, and motivation to children.